Weakly-alkaline MXene urushiol high-heat-resistant anticorrosive coating and preparation method thereof

Through the preparation of MXene cross-linked uucol resin, a high heat-resistant and anti-corrosion coating is formed using the surface reactivity of MXene, which solves the problems of unused MXene activity and complex and costly preparation of coatings in the prior art, and achieves high efficiency, Economical high temperature corrosion resistance.

CN119177067APending Publication Date: 2024-12-24BEIJING TECH & BUSINESS UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411405740.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing MXene failed to fully utilize its active surface reactivity in anticorrosion coatings, resulting in the lack of heat resistance and corrosion resistance of the coating, and the coating preparation process is complex and costly.

Method used

Using MXene cross-linked uuolol resin, the MXene powder is dispersed by ultrasonic to form a weakly alkaline MXene solution, and combined with uuolol. The cross-linking process is completed through the nucleophilic substitution reaction between the phenolic hydroxyl group and the MXene blocked hydroxyl group, forming a high heat resistance and corrosion resistance. Coating, simplify the coating preparation process and reduce costs.

Benefits of technology

Achieve high-strength, high-temperature resistant anti-corrosion coating, simplifies the coating preparation process, reduces the amount of organic solvents, and does not require additional curing. The coating can withstand high temperatures of 200°C, and is suitable for high-temperature equipment, expanding MXene's application in the field of anti-corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177067A_ABST
    Figure CN119177067A_ABST
Patent Text Reader

Abstract

The invention discloses a weakly-alkaline MXene urushiol high-heat-resistant anticorrosive coating and a preparation method thereof. According to the urushiol-MXene high-heat-resistance anticorrosive coating and the preparation method thereof disclosed by the invention, by virtue of the excellent chemical activity of diverse end-capped surfaces of transition metal carbide, nitride or carbonitride (MXene) nanosheets, a cross-linking process is completed through nucleophilic substitution reaction between phenolic hydroxyl groups in urushiol molecules and MXene end-capped hydroxyl groups subjected to weakly alkaline treatment, so that the urushiol-MXene high-heat-resistance anticorrosive coating is formed. The preparation method of the coating is simple and convenient, greatly reduces the dosage of an organic solvent, does not need an additional curing link, and is high in practicability. The MXene nanosheets dispersed in the urushiol matrix of the coating can efficiently block oxygen and water, so that the coating is endowed with extremely high corrosion resistance, long-term protection on various metal substrates is realized, and the practical application of MXene is expanded. In addition, the obtained coating can resist the high temperature of 200 DEG C, and is suitable for high-temperature working condition equipment such as heavy thick oil gathering and transportation pipelines, heat supply units and heat exchangers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high temperature resistant anticorrosion coating preparation, and specifically relates to a weakly alkaline MXene urushiol high heat resistant anticorrosion coating and a preparation method thereof. Background Art

[0002] Urushiol is a natural polyphenol extracted from the secretion of lacquer tree. It is a catechol derivative. Its structural feature is that the 3-position is substituted by a saturated or unsaturated hydrocarbon chain with 15 or 17 carbon atoms. Due to its excellent film-forming property and chemical stability, lacquer phenol has been widely used in the field of functional coatings. Urushiol coatings not only show excellent anti-corrosion properties in the oil and gas industry, marine engineering and industrial equipment, but are also used as important decorative materials in home coatings.

[0003] Two-dimensional transition metal carbides, nitrides and carbonitrides (MXene) have shown broad application prospects in electrochemical energy storage, electromagnetic interference shielding, sensing, catalysis and anti-corrosion coatings due to their metal-like conductivity, high aspect ratio, full-band electromagnetic wave absorption, excellent hydrophilicity and adjustable surface end groups. With the high specific surface area and barrier properties of MXene, it has been used as a nanofiller in coatings to enhance the mechanical properties and anti-corrosion ability of the coating. However, MXene is often regarded as a barrier filler added to inert resins such as epoxy resin and polyurethane to form an anti-corrosion coating, without fully utilizing its active surface reactivity. Summary of the invention

[0004] The purpose of the present invention is to provide a weakly alkaline MXene lacquer phenol high heat-resistant anticorrosion coating and a preparation method thereof. The present invention adopts MXene cross-linked lacquer phenol resin to construct a high heat-resistant anticorrosion coating. The MXene surface has extremely rich cross-linking sites, so the cross-linking efficiency is significantly improved, and the cross-linking process only removes water molecules, and finally forms a high-strength heat-resistant anticorrosion coating. This efficient cross-linking process makes the coating preparation process simple and the total amount of MXene is low, which effectively suppresses the increase in coating cost. In addition, the MXene nanosheets dispersed in the lacquer phenol matrix still retain excellent barrier properties, thereby giving the coating extremely high anticorrosion properties.

[0005] The preparation method of the weakly alkaline MXene urushiol high heat-resistant anticorrosive coating is: ①Ultrasonic dispersion of MXene powder in 0.01-0.2 mol / L alkaline solution at 140-300 W power, the effective concentration of MXene is controlled at 0.05-0.5 mg / mL, and after forming a uniform colloidal solution, ultrasonication is continued for 5-25 min to obtain a weakly alkaline MXene solution; ② Add a highly polar organic solvent to the weakly alkaline MXene solution at a volume ratio of 5-50%, and stir evenly at 200-700r / min; ③ Prepare a xylene solution of urushiol with a mass fraction of 30%-70%, and then add the mixed solution obtained in step ②, wherein the mass ratio of weakly alkaline MXene to urushiol is 1:1500-3000, and stir the slurry at 3500-8000r / min for 0.5-2h to obtain a weakly alkaline MXene urushiol high heat-resistant anti-corrosion coating.

[0006] The MXene is Ti3C2T x , Ti2CT x , Ti3N2T x , Ti3CNT x , V2CT x , Nb2CT x T represents one or more of the end-capping groups = O, -F, -OH, x The value of is 1 or 2.

[0007] The alkaline solution is NaOH or KOH solution.

[0008] The highly polar organic solvent is N -methylpyrrolidone, N - one or more of methylformamide, dimethyl sulfoxide, propylene carbonate.

[0009] The method for using the weakly alkaline MXene lacquer phenol high heat-resistant anti-corrosion coating is as follows: apply the weakly alkaline MXene lacquer phenol high heat-resistant anti-corrosion coating on the surface of the metal substrate with a coating thickness of 75-150 μm; then vacuum dry at 60-90 °C for 2-10 hours to obtain a weakly alkaline MXene cross-linked lacquer phenol high heat-resistant anti-corrosion coating.

[0010] The metal substrate is carbon steel, tinplate, aluminum or copper.

[0011] The present invention uses the excellent surface multi-capping chemical activity of transition metal carbide, nitride or carbonitride (MXene) nanosheets to complete the cross-linking process through the nucleophilic substitution reaction between the phenolic hydroxyl group in the lacquer phenol molecule and the MXene capping hydroxyl group (such as Nb-OH) after weak alkalinity treatment, thereby forming a lacquer phenol-MXene high heat-resistant and anti-corrosion coating. The preparation method of the coating is simple, greatly reduces the amount of organic solvent used, does not require an additional curing step, and has strong practicality. The obtained coating can withstand a high temperature of 200°C and is suitable for high-temperature working equipment such as heavy oil gathering and transportation pipelines, heating units, and heat exchangers. The MXene nanosheets dispersed in the lacquer phenol matrix of the coating can effectively block oxygen and water, achieve long-term protection for a variety of metal substrates, and expand the practical application of MXene. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Schematic diagram of weakly alkaline MXene cross-linking urushiol molecules.

[0013] Figure 2 Tetrabutyl titanate and weakly alkaline Ti3C2T x Electrochemical impedance spectroscopy (Bode mode value plot) of the cross-linked urushiol coating after immersion in 3.5% NaCl solution at 200°C for 30 days.

[0014] Figure 3 Electrochemical impedance spectrum (Bode modulus diagram) of the urushiol coating cross-linked with tetrabutyl titanate and the weakly alkaline mixed MXene of Example 8 after immersion in a 3.5% NaCl solution at 200°C for 30 days. DETAILED DESCRIPTION Example 1

[0015] Ti3C2O2 powder was dispersed in 0.1 mol / L NaOH solution by ultrasound (power 150W) to form a 0.1 mg / mL MXene colloidal solution, and then ultrasound was continued for 10 minutes; then 10% by volume was added N -methylpyrrolidone, stirred evenly at 300 r / min; then added 50% mass fraction of urushiol xylene solution, in which the mass ratio of weakly alkaline Ti3C2O2 to urushiol was 1:1500, and homogenized at 5000 r / min for 1h to obtain the weakly alkaline MXene urushiol high heat-resistant anti-corrosion coating.

[0016] The paint was applied on the carbon steel surface and surrounding areas with a thickness of 100 μm and vacuum dried at 80°C for 5 h.

[0017] The obtained coated samples were placed in an autoclave containing 3.5% NaCl solution and immersed at 200°C for 30 days. The electrochemical impedance spectroscopy test showed that the low-frequency impedance of the samples was 10 9 Ω·cm 2 Above (if attached) Figure 2 as shown). Example 2

[0018] Ti2C(OH)2 powder was dispersed in 0.05 mol / L KOH solution by ultrasonication (power 140W) to form a 0.2 mg / mL MXene colloidal solution, and then ultrasonication was continued for 15 minutes. Then 20% N-methylformamide, stirred at 400 r / min. Then, a 40% mass fraction of urushiol xylene solution was mixed into the above solution, the mass ratio of weakly alkaline Ti2C(OH)2 to urushiol was 1:1750, and the slurry was homogenized at 6000 r / min for 0.5h to obtain a weakly alkaline MXene urushiol high heat-resistant anticorrosion coating.

[0019] The slurry was brushed on the tinplate surface and surrounding areas with a coating thickness of 120 μm and vacuum dried at 70°C for 10 h.

[0020] The coated samples were placed in an autoclave containing 3.5% NaCl solution and immersed at 155°C for 30 days. The electrochemical impedance spectroscopy test showed that the low-frequency impedance of the samples was 10 9 Ω·cm 2 The anti-corrosion effect is better than that of the traditional urushiol coating cross-linked with tetrabutyl titanate. Example 3

[0021] Select an equal mass mixed powder of Ti3N2F2 and V2CF2, disperse it in a 0.1 mol / L KOH solution by ultrasound (power 200W) to form a 0.3 mg / mL colloidal solution, and continue ultrasound for 25 minutes. Then, add 30% dimethyl sulfoxide to the above solution and stir evenly at 300 r / min. Then, add a 40% xylene solution of urushiol to the above solution, the mass ratio of weakly alkaline MXene to urushiol is 1:2500, and homogenize at 7000 r / min for 1.5h to obtain a weakly alkaline MXene urushiol high heat-resistant anticorrosion coating.

[0022] The slurry was brushed on the aluminum surface and surrounding areas with a coating thickness of 125 μm and vacuum dried at 70°C for 8 h.

[0023] The coated samples were placed in an autoclave containing 3.5% NaCl solution and immersed at 90°C for 30 days. The electrochemical impedance spectroscopy test showed that the low-frequency impedance of the samples was 10 10 Ω·cm 2 above. Example 4

[0024] Use V2CO2 powder and disperse it in 0.1 mol / L NaOH solution by ultrasound (power 260W) to form a colloidal solution of 0.25 mg / mLMXene, and continue ultrasound for 22 minutes. Then, mix 25% dimethyl sulfoxide and propylene carbonate mixed solvent (two solvents of equal volume) into the above solution and stir evenly at 700 r / min. Then mix 55% urushiol xylene solution into the above solution, the mass ratio of weakly alkaline V2CO2 to urushiol is 1:2750, and homogenize at 7500 r / min for 1.7h to obtain weakly alkaline MXene urushiol high heat-resistant anticorrosion coating.

[0025] The slurry was brushed on the copper surface and surrounding areas with a coating thickness of 110 μm and vacuum dried at 75°C for 6 h.

[0026] The coated samples were placed in an autoclave containing 3.5% NaCl solution and immersed at 200°C for 30 days. The electrochemical impedance spectroscopy test showed that the low-frequency impedance of the samples was 10 9 Ω·cm 2 above. Example 5

[0027] Nb2C(OH)2 and Ti3N2(OH)2 were mixed powders of equal weight and dispersed in a 0.05 mol / L NaOH solution by ultrasonication (power 220W) to form a 0.35 mg / mL MXene colloidal solution. The ultrasonication was continued for 17 min. Then, 40% N -Methylformamide and dimethyl sulfoxide mixed solvent (two solvents of equal volume), stirred at 450 r / min. Then, a 65% xylene solution of urushiol was mixed into the above solution, and the mass ratio of weakly alkaline MXene to urushiol was 1:1625, and the homogenization was carried out at 6500 r / min for 1.4 hours.

[0028] The slurry was brushed on the copper surface and surrounding areas with a coating thickness of 135 μm and vacuum dried at 65°C for 7 h.

[0029] The coated samples were placed in an autoclave containing 3.5% NaCl solution and immersed at 100 °C for 30 days. The electrochemical impedance spectroscopy test showed that the low-frequency impedance of the samples was 10 10 Ω·cm 2 above. Example 6

[0030] Ti3CN(OH)2 powder was selected and dispersed in 0.1 mol / L KOH solution by ultrasound (power 250 W) to form a 0.15 mg / mL MXene colloidal solution, and the ultrasound was continued for 25 minutes. Then 35% propylene carbonate was mixed into the above solution and stirred evenly at 550 r / min. Then 45% urushiol xylene solution was mixed into the above solution, the mass ratio of weakly alkaline Ti3CN(OH)2 to urushiol was 1:1875, and the weakly alkaline MXene urushiol high heat-resistant anticorrosion coating was obtained by homogenization at 8000 r / min for 2 hours.

[0031] The slurry was brushed on the tinplate surface and surrounding areas with a coating thickness of 120 μm and vacuum dried at 85°C for 2 h.

[0032] The coated samples were placed in an autoclave containing 3.5% NaCl solution and immersed at 180 °C for 30 days. The electrochemical impedance spectroscopy test showed that the low-frequency impedance of the samples was 10 9 Ω·cm 2 above. Example 7

[0033] Nb2CF2 powder was dispersed in a 0.02 mol / L KOH solution by ultrasonication (power 270 W) to form a 0.45 mg / mL MXene colloidal solution, which was ultrasonicated for 16 min. Then, 45% N -Methyl pyrrolidone, stirred at 350 r / min. Then mixed with 35% mass fraction of urushiol xylene solution, the mass ratio of weakly alkaline Nb2CF2 to urushiol was 1:1625, and homogenized at 7000 r / min for 1h to obtain weakly alkaline MXene urushiol high heat-resistant anticorrosion coating.

[0034] The slurry was brushed on the carbon steel surface and surrounding areas with a coating thickness of 80 μm and vacuum dried at 60°C for 4 h.

[0035] The coated samples were placed in an autoclave containing 3.5% NaCl solution and immersed at 95 °C for 30 days. The electrochemical impedance spectroscopy test showed that the low-frequency impedance of the samples was 10 9 Ω·cm 2 above. Example 8

[0036] An equal mass mixed powder of Ti3CNF2 and Nb2CF2 was used, and ultrasonic (power 140 W) was dispersed in a 0.05 mol / L NaOH solution to form a 0.5 mg / mL MXene colloidal solution, and the ultrasonic treatment was continued for 12 minutes. Then 35% dimethyl sulfoxide was mixed into the above solution and stirred evenly at 200 r / min. Then a 70% urushiol xylene solution was mixed, and the mass ratio of weakly alkaline MXene to urushiol was 1:2500. The weakly alkaline MXene urushiol high heat-resistant anticorrosion coating was obtained by homogenizing at 6800 r / min for 1 hour.

[0037] The slurry was brushed on the aluminum surface and surrounding areas with a coating thickness of 140 μm and vacuum dried at 90°C for 2 h.

[0038] The coated samples were placed in an autoclave containing 3.5% NaCl solution and immersed at 200 °C for 30 days. The electrochemical impedance spectroscopy test showed that the low-frequency impedance of the samples was 10 9 Ω·cm 2 Above (if attached) Figure 3 as shown). Example 9

[0039] An equal mass mixed powder of Ti3C2O2 and V2CF2 was used, and ultrasonic (power 190 W) was dispersed in a 0.05 mol / L NaOH solution to form a 0.3 mg / mL MXene colloidal solution, and the ultrasonic treatment was continued for 20 minutes. Then 40% propylene carbonate was mixed into the above solution, and stirred evenly at 450 r / min. Then a 55% mass fraction of urushiol xylene solution was mixed, and the mass ratio of weakly alkaline MXene to urushiol was 1:2800. The weakly alkaline MXene urushiol high heat-resistant anticorrosion coating was obtained by homogenizing at 5500 r / min for 1 hour.

[0040] The slurry was brushed on the copper surface and surrounding areas with a coating thickness of 135 μm and vacuum dried at 75°C for 4 h.

[0041] The coated samples were placed in an autoclave containing 3.5% NaCl solution and immersed at 125 °C for 30 days. The electrochemical impedance spectroscopy test showed that the low-frequency impedance of the samples was 10 10 Ω·cm 2 above. Example 10

[0042] An equal mass of mixed powder of Ti3C2(OH)2 and Ti2C(OH)2 was dispersed in a 0.1 mol / L KOH solution by ultrasonication (power 250 W) to form a 0.4 mg / mL MXene colloidal solution, and ultrasonication was continued for 10 min. Then, 25% N -methylformamide, stirred at 380 r / min. Then mixed with 50% urushiol xylene solution, in which the mass ratio of weakly alkaline MXene to urushiol was 1:3000, and homogenized at 6000 r / min for 1.5h to obtain weakly alkaline MXene urushiol high heat-resistant anticorrosion coating.

[0043] The slurry was brushed on the tinplate surface and surrounding areas with a coating thickness of 120 μm and vacuum dried at 85°C for 2 h.

[0044] The coated samples were placed in an autoclave containing 3.5% NaCl solution and immersed at 100 °C for 30 days. The electrochemical impedance spectroscopy test showed that the low-frequency impedance of the samples was 10 9 Ω·cm 2 above.

Claims

1. A method for preparing a weakly alkaline MXene urushiol high heat-resistant anticorrosive coating, characterized in that: The specific steps of the preparation method are: ①Ultrasonic dispersion of MXene powder in 0.01-0.2 mol / L alkaline solution at 140-300 W power, the effective concentration of MXene is controlled at 0.05-0.5 mg / mL, and after forming a uniform colloidal solution, ultrasonication is continued for 5-25 min to obtain a weakly alkaline MXene solution; ② Add a high-polarity organic solvent to the weakly alkaline MXene solution at a volume ratio of 5-50%, and stir evenly at 200-700r / min; ③ Prepare a xylene solution of urushiol with a mass fraction of 30%-70%, and then add the mixed solution obtained in step ②, wherein the mass ratio of weakly alkaline MXene to urushiol is 1:1500-3000, and stir the slurry at 3500-8000r / min for 0.5-2h to obtain a weakly alkaline MXene urushiol high heat-resistant anti-corrosion coating.

2. The preparation method according to claim 1, characterized in that: The MXene is Ti3C2T x , Ti2CT x , Ti3N2T x , Ti3CNT x , V2CT x , Nb2CT x T represents one or more of the end-capping groups = O, -F, -OH, x The value of is 1 or 2.

3. The preparation method according to claim 1, characterized in that: The alkaline solution is NaOH or KOH solution.

4. The preparation method according to claim 1, characterized in that: The highly polar organic solvent is N -methylpyrrolidone, N - one or more of methylformamide, dimethyl sulfoxide, propylene carbonate.

5. A method for using a weakly alkaline MXene urushiol high heat-resistant anticorrosive coating, characterized in that: The specific operation of the method of use is: applying the weakly alkaline MXene lacquer phenol high heat-resistant anti-corrosion coating prepared by the method described in any one of claims 1 to 4 to the surface of the metal substrate, with a coating thickness of 75-150 μm; then vacuum drying at 60-90 °C for 2-10 hours to obtain a weakly alkaline MXene cross-linked lacquer phenol high heat-resistant anti-corrosion coating.

6. The method of use according to claim 5, characterized in that: The metal substrate is carbon steel, tinplate, aluminum or copper.

Citation Information

Patent Citations

  • Preparation method of graphene composite anticorrosive coating

    CN113088117A

  • Nanosheet composite coating as well as preparation method and application thereof

    CN113621300A

  • Preparation and application of multifunctional self-cleaning MXene-based photo-thermal protective coating

    CN115011239A

  • Two-dimensional material modified raw lacquer marine anticorrosive coating and preparation method thereof

    CN115386255A

  • High-flame-retardance modified epoxy resin and preparation method thereof

    CN118185236A